Tandem Synthesis of Benzo[b]carbazoles and Their Photoluminescent Properties. Issue 38 (9th August 2013) - Xing, Yanpeng; Hu, Binbin; Yao, Qijun; Lu, Ping; Wang, Yanguang
Abstract 5 H‐Benzo[b]carbazoles were prepared through a tandem reaction between 2‐ethynyl‐N‐triphenylphosphoranylidene anilines and α‐diazoketones through ketenimine intermediates in moderate‐to‐good yields. By using this approach, benzo[b]benzo[5, 6]indolo[3, 2‐h]carbazoles, fluoreno[9, 1‐ab]carbazoles, and fluoreno[9, 1‐ab]fluoreno[1′, 9′:5, 6, 7]indolo[3, 2‐h]carbazoles were constructed in one pot. Moreover, the resulting products emitted light within the range 410–521 nm, with quantum yields of up to 62 %.